Ser formador e ser professor sem álibis: o processo formativo de professores de língua inglesa - Fighera, Adriana Claudia Martins (2014)
This study is in the Formation, Knowledge and Professional Development Research Line, of the Post-graduation Program on Education of the Federal University of Santa Maria (UFSM), Rio Grande do Sul, Brazil. This paper intends to understand how educators of teachers from the English Language Course from the Federal University of Santa Maria work as docents and the theoretical-practical conceptions, which guide the dynamic of their activities. For this purpose, knowing the formative, personal and professional path from five educators, we seek to identify the comprehension these professionals have of their own role as educators of the English language teachers and how they work, reflect and think about the teaching responsibility when acting on the formative process of these teachers, regarding their relationship with the students and conceptions related to English language course teaching. This study aims the qualitative research principles from the social-historical cultural narrative approach. The authors Bakhtin/Volochínov (2010), Bakhtin (1981, 2010a, 2010b), Vygotski (1998, 2004, 2007) and Freire (1983, 1995, 1996, 2001, 2008, 2011) corroborate on this investigative study and the theoretical-analytic discussion which was based on three categories: the process of self-identification on the educator being formation, the dynamics of the educator s performance and the qualification of the formative process of the English language teacher. The research allowed us to point out that the grasp of consciousness happens from the interaction of other people s consciousness, which is based on by one specific axiological dimension. Thus, the docent collaborators revealed the necessity of interformation, the appreciation of time inside class as a singular moment for interaction and they understand there is a co-responsibility between educators and students during the initial formative process of English language teachers. From this point of view, the educator being and the teacher being during his initial formation are two subjects from the same process without alibis in this being. We highlight that it is the grasp of consciousness, which allows us to look at the Other s place as someone that we are involved with and that is involved with us. In order to extend our grasp of consciousness we need to be responsible for the Other, being in relationships of commitment. We also highlight that revisited paths and previous experiences contributed for educators to reflection of teaching, attributing meanings to experiences and relationships with the Other.